The possible role of EBV in carcinogenesis of colorectal carcinoma. - habib, Manal A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Except for the tight correlation to nasopharyngeal carcinoma, accumulating evidences show that Epstein-Barr virus (EBV) is correlated to other carcinomas. This study was to investigate the association of EBV with colorectal tumors.Materials & methods: Forty paraffin embedded blocks of colorectal tumors (thirty were adenocarcinoma and ten were benign tumors) were all examined for the presence of EBV DNA withthe application of In Situ hybridization.Results: In Situ EBV DNA signals was detected in 6 out of 30 (20%) of colorectal carcinoma with no observed signals in the sections from benign group.Conclusion: Our results showed that infection of EBV exists in human colorectal adenocarcinoma, which indicates that EBV may be involved in the carcinogenesis process.